Entrepreneurial orientation and supply chain resilience of manufacturing SMEs in Yemen: the mediating effects of absorptive capacity and innovation - Mohammed A. Al-Hakimi; Moad Hamod Saleh; Dileep B. Borade (Heliyon, 2021)
Literature has revealed, recently, the importance of entrepreneurial orientation (EO) for supply chain resilience (SCR); however, doubts remain as to how EO could improve SCR exist due to the vagueness surrounding it. We examine absorptive capacity (AC) and innovation as two mechanisms that mediate the EO-SCR relationship. An empirical analysis was made of the proposed model, based upon survey data for 171 manufacturing SMEs in the Sana'a region, Yemen, using a structural equation model (SEM) with the SmartPLS. The results obtained have shown that EO positively affects SCR for SMEs and, most significantly, this relationship is indirect as it is fully mediated by AC and innovation. The findings have revealed that EO improves SCR when those firms make efforts in developing AC and innovation. EO is significant, but it may not be sufficient to improve SCR if the firm is unable to absorb external knowledge and innovate.